Comparison of structural dynamics and coherence of d–d and MLCT light-induced spin state trapping. Issue 7 (17th May 2017) - Zerdane, S.; Wilbraham, L.; Cammarata, M.; Iasco, O.; Rivière, E.; Boillot, M.-L.; Ciofini, I.; Collet, E.
Abstract : Femtosecond optical spectroscopy revealed that the coherent structural dynamics accompanying LIESST was stronger with d–d than MLCT excitation. Abstract : Light-induced excited spin state trapping (LIESST) in Fe II spin-crossover systems is a process that involves the switching of molecules from low (LS, S = 0) to high spin (HS, S = 2) states. The direct LS-to-HS conversion is forbidden by selection rules, and LIESST involves intermediate states such as 1, 3 MLCT or 1, 3 T. The intersystem crossing sequence results in an HS state, structurally trapped by metal–ligand bond elongation through the coherent activation and damping of molecular breathing. The ultrafast dynamics of this process has been investigated in FeN6 ligand field systems, under MLCT excitation. Herein, we studied LIESST in an Fe II N4 O2 spin-crossover material of lower symmetry, which allowed for quite intense and low-energy shifted d–d bands. By combining ab initio DFT and TD-DFT calculations and fs optical absorption measurements, we demonstrated that shorter intermediates enhanced coherent structural dynamics, and d–d excitation induced faster LS-to-HS switching, compared to MLCT.